A new report of three parasitoids of the cogongrass gall-midge Orseolia javanica Kieffer & Van Leeuwen-Reijnvaan (Diptera: Cecidomyiidae) in Bogor West Java. Issue 1 (December 2021) - Maqalina, M N; Harahap, I S; Hidayat, P
Abstract: The cogongrass gall midge, Orseolia javanica, has been identified as a biological control agent with the ability to specifically attack cogongrass ( Imperata cylindrica ) or known in Indonesia as alang-alang. However, in the field, the cogongrass gall midge has a high parasitism by insect parasitoids, which could lead to population collapse. Information regarding the insect parasitoids of the cogongrass gall midge is a very limited. The objectives of this study was to describe and identify the new reported cogongrass gall midge parasitoids in Gunung Gadung cemetery in Cipaku, South Bogor District, Bogor. This study was conducted by taking the cogongrass galls in the field, maintaining in the laboratory, identificating the parasitoids, and calculating the percentage of parasitism. The study has been conducted from August 2020 to May 2021. Three new reported parasitoids were identified on O. javanica in addition to five already known parasitoid, they were Eurytoma sp. (Hymenoptera: Eurytomidae), Lamprotatus sp. (Hymenoptera: Pteromalidae), and Nigeriella sp. (Hymenoptera: Agaonidae). These parasitoids may be able to reduce the effectiveness of the cogongrass gall-midge in controlling the cogongrass. Their morphological characters, descriptions, and percentage of parasitism are presented.